Fire drives phylogenetic clustering in Mediterranean Basin woody plant communities - VERDÚ, M; PAUSAS, J.G (The Journal of ecology, 2007)
1. Many Mediterranean plant species persist after fire because their seeds are protected from the heat of the fire (e.g. hard-coated seeds, serotinous cones), thus permitting rapid post-fire recruitment. For simplicity, this trait will hereafter be called P and its two possible phenotypes P+ (seeder) and P- (non-seeder). 2. Because P+ appears in a narrow taxonomic spectrum and confers persistence under high fire frequencies, we test the extent to which communities with different fire histories have different phenotypic and phylogenetic structures. Specifically, we compare coastal vegetation growing in a warm and dry Mediterranean climate subject to high fire frequency (HiFi vegetation) with montane vegetation subject to a subhumid climate where fires are rare (LowFi) under the hypothesis that P+ species will be over-represented in HiFi communities, thus producing phenotypic and phylogenetic clustering. 3. Trait conservatism on P is evaluated by testing the presence of a phylogenetic signal, phenotypic clustering is tested by correlating co-occurrence and phenotypic distance matrices, and the phylogenetic structure is evaluated by testing whether the phylogenetic distances between species in each community are different from those expected by chance. 4. The results suggest that: (a) P is a strongly conserved trait; (b) co-occurring species have similar P phenotypes (phenotypic clustering); and (c) the phylogenetic structure in HiFi vegetation is significantly clustered while LowFi vegetation tends to be overdispersed. 5. Synthesis: Fire is a strong driving force in assembling HiFi communities while other forces, such as competitive interactions, are the main assembly mechanisms in LowFi communities. This result supports the role of recurrent disturbances as filters driving phylogenetic community structure.